2009
DOI: 10.1152/jn.90702.2008
|View full text |Cite
|
Sign up to set email alerts
|

Complex Unconstrained Three-Dimensional Hand Movement and Constant Equi-Affine Speed

Abstract: Maoz U, Berthoz A, Flash T. Complex unconstrained threedimensional hand movement and constant equi-affine speed. J Neurophysiol 101: 1002-1015, 2009. First published December 10, 2008 doi:10.1152/jn.90702.2008. One long-established simplifying principle behind the large repertoire and high versatility of human hand movements is the two-thirds power law-an empirical law stating a relationship between local geometry and kinematics of human hand trajectories during planar curved movements. It was further general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 53 publications
(75 reference statements)
5
47
1
Order By: Relevance
“…However, this Euclidean interpretation does not hold, and the earlier results of Viviani and Stucchi (1992) and LevitBinnun et al (2006) and recent findings on 3D movement production (Pollick et al 2009;Maoz et al 2009) together with our results here suggest that the most parsimonious interpretation of planar and spatial results may be found in the nonEuclidean equi-affine framework, or even more general and abstract geometries (Bennequin et al 2009). As was demonstrated over the last decade and a half, the many phenomena apparently obeying the two-thirds power law, in both motion perception and production, can all be alternatively explained as stemming from the simplest equi-affine-geometric invariant: movement at constant equi-affine speed Handzel 1996, 2007;Handzel and Flash 1999;Bennequin et al 2009).…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…However, this Euclidean interpretation does not hold, and the earlier results of Viviani and Stucchi (1992) and LevitBinnun et al (2006) and recent findings on 3D movement production (Pollick et al 2009;Maoz et al 2009) together with our results here suggest that the most parsimonious interpretation of planar and spatial results may be found in the nonEuclidean equi-affine framework, or even more general and abstract geometries (Bennequin et al 2009). As was demonstrated over the last decade and a half, the many phenomena apparently obeying the two-thirds power law, in both motion perception and production, can all be alternatively explained as stemming from the simplest equi-affine-geometric invariant: movement at constant equi-affine speed Handzel 1996, 2007;Handzel and Flash 1999;Bennequin et al 2009).…”
Section: Discussioncontrasting
confidence: 80%
“…We have recently shown that constant equi-affine speed generalizes to 3D and that 3D movement at constant equi-affine speed entails a power law different from the two-thirds power law. Moreover, general self-paced unconstrained scribbling and shape-tracing hand movements in 3D both seem to be produced at roughly constant spatial (3D) equi-affine speed (Pollick et al , 2009Maoz et al 2009).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The same dimensionless representation may also be useful in analyzing other scale-invariant features and reveal spectrum of power laws in other motor contexts. Power laws have indeed been observed in many types of movements, including 3D hand movements (16), smooth pursuit eye movements (17), speech (18), and walking (19), and also appear in visual motion perception (20).…”
Section: Discussionmentioning
confidence: 92%
“…e* = a 1 a 2 = I 1 ðνÞ 2I 2 ðνÞ , [16] which is a decreasing function of ν with a minimum lim ν→∞ e * = 32=17 (Fig. 9).…”
Section: Appendix B: Euler-lagrange Equation In Angle Coordinatementioning
confidence: 94%